PUBLIKASI CAGAR BUDAYA UNTUK PARIWISATA - Sugeng Riyanto (Balai Arkeologi Provinsi Sulawesi Utara, 2018)
Archaeological data has a value that is unique but broad aspects includes research, preservation, and utilization. Research and preservation is a basic process that each one has a specific framework and reciprocal. The results of the research-preservation process is the information and knowledge about the past that is supported by the physical appearance of archaeological data. Thus, the data of archaeological or cultural heritage has the potential utilization related to tourism. In the framework of information development will be very important that needed special attention. This paper was prepared to give an idea about information development of archaeological data or cultural heritage relating to tourism.